The Immunization Status and Nutritional Knowledge Level of the Mother Influence the Nutritional Status of Toddlers in the Nambo Primary Health Care Working Area, Kendari City - Milati Hamidah; Sulastrianah; Nina Indriyani Nasruddin (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Due to their golden age of physical development and intelligence, infants nutritional status requires special consideration. Preliminary investigations at the Nambo Primary Health Care found that 19 toddlers suffered from wasted, with four being severely wasted. Purpose: The purpose of this study is to examine the influence of the toddler's immunization status and the mother's level of nutritional education on the nutritional status of infants in the Nambo Primary Health Care working area. Methods: This study utilized a case-control design in the Nambo Primary Health Care working area from November to December 2022. This investigation included 69 toddlers as participants (23 toddlers in the case group and 46 toddlers in the control group). We gathered data by administering a questionnaire and measuring the toddler's weight and height, which we analyzed using the chi-square test and Fisher’s Exact test. Results: Results indicated that immunization status significantly influences the nutritional status of infants (OR = 4.594; p = 0.034; 95% CI: 1.183–17.840). The mother's nutritional knowledge has a significant effect on the nutritional status of toddlers (OR = 10.587; p = 0.000; 95% CI = 3.118–37.818). Conclusions: The nutritional status of toddlers in the Nambo Primary Health Care Working Area, Kendari City, is influenced by the nutritional knowledge and vaccination status of their mothers.